Enhancing Rice Yield and Weed Management in Direct Seeded Rice Using Ammonium Sulfate as Adjuvant with Lower Dose of Early Postemergence Herbicides - Wajid Saeed; Saif Ullah; Abdul Khaliq; Fazal Munsif; Izhar Ali; Tahir Hussain Jandan; Anas Iqbal; Pingwu Liu (AGRIVITA, Journal of Agricultural Science, 2021)
A field experiment was conducted in 2016 to find out the sequential use of different herbicides with adjuvants (a substance which enhances pesticides efficiency) towards improved rice production and weed management in direct-seeded rice crop. The early postemergence herbicides (Kelion 50 WG, Ryzelan 240 SC, and Nominee 100 SC were applied at full or 75% of the full dose with and without adjuvants i.e. 2% solution of ammonium sulfate (AS) and alkyl ether sulfate (AES) at 14 days after sowing (DAS), followed by late postemergence herbicides i.e. Puma super (7.5 EW) and Sunstar 60 WG at 28 DAS. Application of herbicides with and without adjuvant substantially suppressed weed with weed dry weight at 40 and 60 DAS and improved rice yield attributes over a weedy check. It was found that a combination of 75% of Nominee 100 SC along with adjuvant i.e. AS (2% v/v) resulted in higher biological yield (9.16 t/ha), harvest index (30.65%), more grains per panicle (98.13), 1000 grain weight (21.32 g) with improved seed yield (3.86 t/ha). Also, abortive kernel (5.33), chalky kernels (5.66), opaque kernels (5.00), normal kernel (70.66), water absorptive ratio (4.28), and kernel length (10.13).